2002
DOI: 10.1523/jneurosci.22-03-00854.2002
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Inhibits Neurite Outgrowth and Branching of Hippocampal Neurons by a Rho-Dependent Mechanism

Abstract: In response to injury and inflammation of the CNS, brain cells including microglia and astrocytes secrete tumor necrosis factor-alpha (TNF). This pro-inflammatory cytokine has been implicated in both neuronal cell death and survival. We now provide evidence that TNF affects the formation of neurites. Neurons cultured on astrocytic glial cells exhibited reduced outgrowth and branching of neurites after addition of recombinant TNF or prestimulation of glial cells to secrete TNF. This effect was absent in neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
203
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(216 citation statements)
references
References 54 publications
11
203
2
Order By: Relevance
“…At the higher dose (1000 U), IL-1b, IL-6, and TNFa caused a significant reduction in each parameter of dendrite morphology. These findings are consistent with a recent study reporting that TNFa significantly decreased neurite outgrowth and branching of hippocampal neurons in culture (Neumann et al, 2002). Interferon-g also inhibits dendritic growth in hippocampal neurons (Kim et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At the higher dose (1000 U), IL-1b, IL-6, and TNFa caused a significant reduction in each parameter of dendrite morphology. These findings are consistent with a recent study reporting that TNFa significantly decreased neurite outgrowth and branching of hippocampal neurons in culture (Neumann et al, 2002). Interferon-g also inhibits dendritic growth in hippocampal neurons (Kim et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…IL-6 and TNFa can decrease b-catenin expression in hepatocarcinoma cells (Cervello et al, 2001) and in bronchial epithelial cells (Carayol et al, 2002), suggesting that cytokines may act through a mechanism that involves b-catenin in developing dendrites. As noted above, TNFa significantly decreased dendrite development of hippocampal neurons; this effect involved a Rho GTPasedependent mechanism that also regulates the cytoskeleton (Neumann et al, 2002). These studies suggest that regulation of the cytoskeleton is a potential mechanism through which cytokines can inhibit the development of dendrites.…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, our data provide a counterpoint to the effect of TNF␣ or trauma on the activation state of Rho GTPases in neurons (Neumann et al, 2002;Dubreuil et al, 2003). Our results suggest that the initiating signal of a reactive astrogliosis is associated not with activation of Rho GTPases, but, conversely, with their deactivation.…”
Section: Discussionmentioning
confidence: 60%
“…The Rho-ROCK-MLC axis thus appears to be the critical controller of these processes in mammalian systems, in turn suggesting the potential for the involvement of this pathway in the effects of IL-1␤ on astrocyte structure. Interactions between cytokine signaling and small GTPases, including Rho, have been reported in fibroblasts, HeLa cells, and neurons (Puls et al, 1999;Singh et al, 1999, Neumann et al, 2002, but such interactions have not previously been implicated in the generation of a reactive astrogliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TNF-α or glutamate can activate RhoA and Rho kinase [39][40][41]. RhoA is an essential component of the excitotoxicity pathway, and is sufficient to induce the activation of such pathway [42].…”
Section: Discussionmentioning
confidence: 99%